The Future of Software Development: Integrating AI and Machine Learning into the SDLC - Naimil Navnit Gadani (International Journal of Engineering and Management Research, 2024)
The integration of AI and ML into the SDLC represents a groundbreaking advancement in software engineering. This paper explores the transformative effects of AI-driven automation on key stages of the SDLC, including code generation, testing, and deployment. It also examines architectural frameworks that support the effective integration of AI technologies, such as Microservices Architecture, Event-Driven Architecture, and Hybrid Cloud Architecture. By analyzing quantitative improvements and discussing future research directions, the paper provides a comprehensive overview of how AI and ML are shaping the future of software development.